PENGGUNAAN BAHASA INDONESIA UNTUK MELAKUKAN OPERASI DML (DATA MANIPULATION LANGUANGE) - DESIE, HARTANTI; TIONO, HERYANTO (2001)
PENGGUNAAN BAHASA INDONESIA UNTUK MELAKUKAN OPERASI DML (DATA MANIPULATION LANGUANGE)